2011
DOI: 10.3892/mmr.2011.449
|View full text |Cite
|
Sign up to set email alerts
|

TP53 codon 72 polymorphism is associated with pancreatic cancer risk in males, smokers and drinkers

Abstract: Abstract. Tumor protein p53 (TP53) is the best-known tumor suppressor gene and plays a crucial role in carcinogenesis. The TP53 arg 72 Pro polymorphism has been reported to be a risk factor for several types of cancer, but its association with pancreatic cancer has not been fully evaluated. Therefore, we investigated the effects of this polymorphism on pancreatic cancer in relation to smoking and drinking habits by examining the distribution of the SnP genotypes in 226 pancreatic cancer patients and 448 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
(27 reference statements)
0
17
0
Order By: Relevance
“…Furthermore, the Pro/Pro frequency in PDAC was higher in this study using FFPE tissues (65.6%) than in the studies of Sonoyama et al . (14.6%) [9] or Nacaeeati et al . (7.9%) [30] using blood samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the Pro/Pro frequency in PDAC was higher in this study using FFPE tissues (65.6%) than in the studies of Sonoyama et al . (14.6%) [9] or Nacaeeati et al . (7.9%) [30] using blood samples.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was subsequently validated through in vitro DNA-protein binding and reporter plasmid cell-based assays [4]. These polymorphisms were investigated previously in peripheral blood samples from PDAC patients [911]. To our knowledge, in PDAC, no study has examined TP53 codon 72 and only one study has examined the MDM2 SNP 309 [12] polymorphism using formalin-fixed paraffin-embedded (FFPE) specimens.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a significant interaction has been reported between TP53 Pro/Pro genetic polymorphism and smoking in esophageal squamous cell carcinoma (OR = 5.29, 95% CI = 2.91 -9.61) (28). In pancreatic cancer, it was reported that TP53 Pro/Pro genotype significantly increases the risk of cancer among males, particularly among heavy smokers and excessive alcohol drinkers (29). Liu et al also reported that TP53Pro allele increases the risk of squamous cell carcinoma of the lung mainly in heavy smokers (OR = 3.84, 95% CI = 1.46 -10.1) (30).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a mutation occurring in the same location can initiate different cancers depending on the geographical location, ethnic background, and/or gender of the patient. Sonoyama et al investigated P53 proline mutation and found that it caused pancreatic cancer in males, 29 whereas the same mutation decreased the risk of breast cancer in Arab women. 30 Gene markers can assist in the determination of subtypes of cancer.…”
Section: Disease Biomarkers and Postgenomic Technology Cancer Markersmentioning
confidence: 96%